Ultrasound-Assisted Extraction of Bioactive Compounds from Annatto Seeds, Evaluation of Their Antimicrobial and Antioxidant Activity, and Identification of Main Compounds by LC/ESI-MS Analysis (2019)
ABSTRACT: This study evaluated the antimicrobial activity (i.e., against Bacillus cereus and Staphylococcus aureus) and the antioxidant activity (i.e., ABTS, FRAP, and DPPH) ofannatto seeds extract obtained by ultrasound-assisted extraction. A response surface design with three levels such as pH (2-11), solvent concentration (50-96 %), seed-to-solvent ratio (1:2–1:10), and treatment time (0-30min) was employed to determine the optimal experimental conditions. Thus, a pH of 7.0, seed-to-solvent ratio of 1:7, and treatment time of 20 min were selected as optimal rendering an extract having a 0.62% of bixin, 3.81 mg gallic acid/mg equivalent of polyphenol compounds (ABTS 1035.7, FRAP 424.7, and DPPH 1161.5 µM trolox/L), and a minimal inhibitory concentration against Bacillus cereus and Staphylococcus aureus of 32 and 16 mg/L, respectively. Further, the main bioactive compounds identified by LC/ESI-MS were bixin and catechin, chlorogenic acid, chrysin, butein, hypolaetin, licochalcone A, and xanthohumol.